(untitled) - Ferry, Angélique (Comptes Rendus. Chimie)
The importance and ubiquity of glycosides in both compounds of interest and biological processes make these biomolecules an interesting topic of study. The development of unnatural analogues is equally compelling and has already led to the production of several marketed drugs. The discovery of novel carbohydrates is thus a field of interest. In order to open up this chemical space, it is necessary to set up new and efficient synthetic methods, which lead to diverse unnatural glycosides, some of which could become beneficial new compounds. This account deals with the benefits presented by metal-catalyzed reactions, especially cross-couplings and C–H functionalization, to enable glycoside diversity.